Cardiac and Skeletal Muscle Transcriptome Response to Heat Stress in Kenyan Chicken Ecotypes Adapted to Low and High Altitudes Reveal Differences in Thermal Tolerance and Stress Response - Srikanth, Krishnamoorthy; Kumar, Himansu; Park, Woncheoul; Byun, Mijeong; Lim, Dajeong; Kemp, Steve; te Pas, Marinus F. W.; Kim, Jun-Mo; Park, Jong-Eun (Frontiers in Genetics, 2019)
Heat stress (HS) negatively affects chicken performance. Agricultural expansion will happen in regions that experience high ambient temperatures, where fast growing commercial chickens are vulnerable. Indigenous chickens of such regions, due to generations of exposure to environmental challenges might have higher thermal tolerance. In this study, two indigenous chicken ecotypes, from the hot and humid Mombasa (lowland) and the colder Naivasha (highland) regions were used to investigate the effects of acute (5h, 35°C) and chronic (3d of 35°C for 8h/d) heat stress on the cardiac and skeletal muscle, through RNA sequencing. The rectal temperature gain and the number of differentially expressed genes (DEGs) (FDR < 0.05) were two times higher in the acute stage than in the chronic stage in both the ecotypes, suggesting, cyclic exposure to HS can lead to adaptation. A tissue and stage specific difference in response to HS was observed, with PPAR signaling and MAPK signaling pathways, enriched in heart and skeletal muscle respectively and the p53 pathway enriched only in the acute stage in both the tissues. The acute and chronic stage DEGs were integrated by a region specific gene co-expression network (GCN) and genes with the highest number of connections (HUB genes) were identified. The hub genes in the lowland network were CCNB2, Crb2, CHST9, SESN1 and NR4A3, while COMMD4, TTC32, H1F0, ACYP1 and RPS28 were the hub genes in the highland network. Pathway analysis of genes in the GCN showed that p53 and PPAR signaling pathways were enriched in both low and highland networks, while MAPK signaling and Protein processing in endoplasmic reticulum were enriched only in the gene network of highland chickens. This shows that to dissipate the accumulated heat, to reduce heat induced apoptosis and to promote DNA damage repair, the ecotypes activated or suppressed different genes, indicating the differences in thermal tolerance and heat stress response mechanisms between the ecotypes. This study provides information on the HS response of chickens, adapted to two different agro climatic environments, extending our understanding of the mechanisms of heat stress response and the effect of adaptation in counteracting HS.